Louis Agassiz correspondence - Agassiz, Louis, 1807-1873.
Letter of Agassiz addressed to John Clark requesting fifty copies of his eulogy of Alexander von Humboldt.
Zoologist. Full name: Jean Louis Rudolphe Agassiz.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Clark, John -- Correspondence; Humboldt, Alexander von, -- 1769-1859.; Zoologists